Measures to assess quality of postnatal care: A scoping review - Anna Galle; Allisyn C. Moran; Mercedes Bonet; Katriona Graham; Moise Muzigaba; Anayda Portela; Louise Tina Day; Godwin Kwaku Tuabu; Bianca De Sá é Silva; Ann-Beth Moller (Public Library of Science (PLoS), 2023)
High quality postnatal care is key for the health and wellbeing of women after childbirth and their newborns. In 2022, the World Health Organization (WHO) published global recommendations on maternal and newborn care for a positive postnatal care experience in a new WHO PNC guideline. Evidence regarding appropriate measures to monitor implementation of postnatal care (PNC) according to the WHO PNC guideline is lacking. This scoping review aims to document the measures used to assess the quality of postnatal care and their validity. The review was conducted according to the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR). Five electronic bibliographic databases were searched together with a grey literature search. Two reviewers independently screened and appraised identified articles. All data on PNC measures were extracted and mapped to the 2022 WHO PNC recommendations according to three categories: i) maternal care, ii) newborn care, iii) health system and health promotion interventions. We identified 62 studies providing measures aligning with the WHO PNC recommendations. For most PNC recommendations there were measures available and the highest number of recommendations were found for breastfeeding and the assessment of the newborn. No measures were found for recommendations related to sedentary behavior, criteria to be assessed before discharge, retention of staff in rural areas and use of digital communication. Measure validity assessment was described in 24 studies (39%), but methods were not standardized. Our review highlights a gap in existing PNC measures for several recommendations in the WHO PNC guideline. Assessment of the validity of PNC measures was limited. Consensus on how the quality of PNC should be measured is needed, involving a selection of priority measures and the development of new measures as appropriate.